Antioxidant Capacities and Phytoconstituents of Fractions of Ethanol Extract of Cymbopogon citratus (DC.) Stapf: Inhibition of Iron II (Fe2+) - Induced Lipid Peroxidation in Rat Colon Homogenate (African Journal of Biomedical Research, 2020)
Oxidative stress is associated with the generation of excess free radicals and reduction in the levels of antioxidant enzymes. It is also implicated in the initiation and progression of colorectal cancer. Cymbopogon citratus, commonly called ‘lemon grass,’ is widely distributed in the tropics and it is known for its therapeutic applications. In this study, the antioxidant activities of the crude ethanol extract of Cymbopogon citratus and its fractions were determined using total antioxidant capacity (TAC), 2-2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity, Fe3+ reducing ability, total phenolic content (TPC) and total flavonoid content (TFC). The phytocomponents were determined through Gas Chromatography - Mass Spectrometry and lipid peroxidation was induced in rat colon homogenate. TFC and TPC were highest in the ethyl acetate fraction (EAF) > crude extract (CE) > ethanol fraction (EF) > chloroform fraction (CF). Both DPPH scavenging activity and Fe3+ reducing ability exhibited similar trend; EAF > EF > CF > CE. In addition, the ability to inhibit lipid peroxidation in rat colon is as follows; EAF> CF > CE > EF. The EAF and CF of the ethanol extract of C. citratus contain most of the compounds that could be responsible for its activity against reactive oxygen species